2015
DOI: 10.1542/peds.2015-1858
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Metronome in Cardiopulmonary Resuscitation: A Simulation Study

Abstract: Determine whether the use of a metronome improves chest compression rate and depth during cardiopulmonary resuscitation (CPR) on a pediatric manikin.METHODS: A prospective, simulation-based, crossover, randomized controlled trial was conducted. Participants included pediatric residents, fellows, nurses, and medical students who were randomly assigned to perform chest compressions on a pediatric manikin with and without an audible metronome. Each participant performed 2 rounds of 2 minutes of chest compressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 23 publications
2
31
0
3
Order By: Relevance
“…On the AED device, depth accuracy would automatically be calculated at 0% when participants compressed below 5.0 cm or above 6.0 cm. One recent study reported the compression rate was 106.6±17.5 cpm with the metronome sound at 100 times and 112.0±17.1 cpm without the metronome sound 27. A lower mean compression rate was reported of 103.1 cpm with audiovisual feedback and 108.0 cpm without feedback, but the IQR was between 96 and 110 cpm with audiovisual feedback, and 99 and 117 cpm without feedback 16.…”
Section: Discussionmentioning
confidence: 99%
“…On the AED device, depth accuracy would automatically be calculated at 0% when participants compressed below 5.0 cm or above 6.0 cm. One recent study reported the compression rate was 106.6±17.5 cpm with the metronome sound at 100 times and 112.0±17.1 cpm without the metronome sound 27. A lower mean compression rate was reported of 103.1 cpm with audiovisual feedback and 108.0 cpm without feedback, but the IQR was between 96 and 110 cpm with audiovisual feedback, and 99 and 117 cpm without feedback 16.…”
Section: Discussionmentioning
confidence: 99%
“…The group using the metronome persisted longer in the appropriate frequency range than the group that did not use the device, showing that the use of technology and devices can improve care and influence ROSC in real situations 24 .…”
Section: Discussionmentioning
confidence: 93%
“…In CPR simulation studies carried out on untrained bystanders by Rasmussen [14] and Park [8] and in those carried out on trained rescuers by Zimmerman [10], Hafner [9],Chung [18], Kern [7] and Jantti [6], the use of a metronome during CPR was found to increase success rates in terms of reaching target chest compression rates (p-values; 0.04, 0.018, 0.001, 0.002, 0.001, 0.001, and < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the use of a metronome to increase the quality and effectiveness of CPR have also been conducted [5][6][7][8][9][10][11][12][13][14][15][16][17][18].The use of a metronome was shown to be effective in reaching the target compression [6-10, 14, 18] and ventilation rates [5][6][7][8][9][10][11][12][13][14][15][16], and to affect compression depth [6,[8][9][10][12][13][14][15]. However, no definitive conclusions have been reached regarding the effects of metronome use on chest compression and ventilation rates [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%